The Use of Lingsan Media (ASEAN Tour) in Science Learning for Grade VI of Curug State Elementary School to Improve 21st Century Skills - Pamungkas, Bekti Kuat; Wakhudin, Wakhudin (UM Purwokerto Press, 2025)
Education aims to form quality Human Resources so that they can always keep up with developments in the 21st century. 21st century education requires students to have communication, collaboration, critical thinking, creativity, citizenship and character skills. In line with the implementation of the Independent Curriculum which requires students to develop holistically. In the Independent Curriculum we are familiar with science and education learning. Science and education learning aims for students to be able to think critically about nature, develop character and citizenship. In reality, science and education learning in grade VI of Curug State Elementary School experienced obstacles so that it was not successful, especially the ASEAN material. Seeing this reality, the researcher tried to apply Lingsan (ASEAN Tour) media. The purpose of applying this media is to improve 21st century skills. So the purpose of the study is to find out whether the application of Lingsan (ASEAN Tour) media can improve the 21st century skills of Curug State Elementary School students. This study uses qualitative research with a case study method. This study uses observation, interview and documentation techniques to collect data. The data is analyzed descriptively. This study also uses data analysis techniques through data reduction, data presentation and drawing conclusions. And using data validity techniques through the stages of credibility, transferability, accountability and proof. Lingsan Media (ASEAN Tour) was created by utilizing ICT in the form of a laptop. This media is in the form of two ASEAN maps. This media has been proven to improve 21st century skills as seen from the results of observations, interviews and documentation. The results of this study support the development of 21st century skills in elementary schools through digital learning.